Penyelesaian Wanprestasi Pada Perjanjian Jual Beli Tanah Di Pengadilan Negeri Padang (Studi Putusan Perkara Nomor. 46/Pdt.G/2022/PN Pdg) - Dwikornida, Dwikornida; Avied, Hakimu (Fakultas Hukum Universitas Tamansiswa Padang, 2023)
Default can arise due to intentional or negligent commitment to being bound by an agreement and the presence of compelling circumstances. The default between the Plaintiff and Defendant I and Defendant II was a land sale and purchase case where Defendant I and Defendant II did not have the good faith to assist in the process of changing the name of the certificate because they had left their residence so that the Plaintiff could not change the name to the Plaintiff's name. Article 1365 of the Civil Code explains that every act that violates the law and causes loss to another person requires the person who caused the loss through his fault to compensate for the loss. The formulation of the problem is 1) What is the judge's consideration in resolving the default in the land sale and purchase case at the Padang District Court in Case Decision Number. 46/Pdt.G/2022/PN Pdg. 2) To find out the judge's decision in resolving defaults on land sales and purchases at the Padang District Court in Case Decision Number. 46/Pdt.G/2022/PN Pdg. The objectives of the research are 1) To find out the judge's considerations in resolving defaults in land sale and purchase cases at the Padang District Court in Case Decision Number. 46/Pdt.G/2022/PN Pdg. 2) To find out the judge's decision in resolving defaults on land sales and purchases at the Padang District Court in Case Decision Number. 46/Pdt.G/2022/PN Pdg. The benefits of research are theoretical and practical benefits. The research method is normative law and the data source is secondary data. Document study and literature study data collection techniques. Data processing is editing and coding. The analysis technique is qualitative. The results of the research, first: The judge's considerations in resolving default on land sale and purchase cases at the Padang District Court were carried out by accepting, examining and adjudicating the case and the judge decided that the Plaintiff was on the winning side and could change the name of the Ownership Certificate from the name of Defendant I to the name The plaintiff punished Co-Defendant II (BPN) for assisting in the process of changing the name of the certificate. Second: The judge's decision in resolving the default on the sale and purchase of land at the Padang District Court was carried out with a uit voorbaar bij vooraat and a verstek decision so that the Plaintiff was on the winning side and was entitled to a transfer of name certificate and Defendant I and Defendant II were punished jointly to pay costs case amounting to Rp. 2,980,000 (two million nine hundred and eighty thousand rupiah).